2023
DOI: 10.1097/ms9.0000000000000592
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of giant recurrent retroperitoneal liposarcoma: a case report and review of the literature

Abstract: Introduction: Liposarcoma is a rare, primary, malignant mesenchymal tumor. It represents ∼7% of all mesenchymal sarcomas and 1% of all cancers. Their incidence does not exceed to 2.5 cases/million inhabitants/year. This tumor is locally invasive, diagnosed at a late stage, and can reach a significant size and weight, resulting in a locally advanced tumor. Case presentation: A 59-year-old female patient consulting for a large abdominal mass. The abdomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…This approach effectively tracks the recurrence and development of retroperitoneal tumors. Surgical resection with negative margins is widely recognized the primary treatment for RPLPS (18). Studies have demonstrated that resection with clean margins under microscopy (R0 resection) leads to longer postoperative survival compared to resection with positive tumor margins under microscopy (R1 resection) (19).…”
Section: Discussionmentioning
confidence: 99%
“…This approach effectively tracks the recurrence and development of retroperitoneal tumors. Surgical resection with negative margins is widely recognized the primary treatment for RPLPS (18). Studies have demonstrated that resection with clean margins under microscopy (R0 resection) leads to longer postoperative survival compared to resection with positive tumor margins under microscopy (R1 resection) (19).…”
Section: Discussionmentioning
confidence: 99%